2019
DOI: 10.1007/s10096-019-03661-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol abuse affects the clinical course and outcome of community-acquired bacterial meningitis

Abstract: The aim of the study was to determine the effect of chronic alcohol abuse on the course and outcome of bacterial meningitis (BM). We analyzed records of patients with BM who were hospitalized between January 2010 and December 2017 in the largest neuroinfection center in Poland. Out of 340 analyzed patients, 45 (13.2%) were alcoholics. Compared with non-alcoholics, alcoholics were more likely to present with seizures (p < 0.001), scored higher on the Sequential Organ Failure Assessment (SOFA) (p = 0.002) and lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This may lead to increased susceptibility to pathogenesis by infections such as bacterial meningitis ( 23 ). Alcoholism was independently associated with poor outcomes, such as a lower GCS score in meningitis ( 24 ). A previous study demonstrated that alcohol consumption can decrease the trans-epithelial electrical resistance (TER) value, thereby promoting the intestinal translocation of S. suis to the blood and brain in a mouse model ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to increased susceptibility to pathogenesis by infections such as bacterial meningitis ( 23 ). Alcoholism was independently associated with poor outcomes, such as a lower GCS score in meningitis ( 24 ). A previous study demonstrated that alcohol consumption can decrease the trans-epithelial electrical resistance (TER) value, thereby promoting the intestinal translocation of S. suis to the blood and brain in a mouse model ( 25 ).…”
Section: Discussionmentioning
confidence: 99%